2021
DOI: 10.1136/archdischild-2021-322755
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of new cases after a coeliac disease mass screening

Abstract: ObjectiveWe previously performed a population-based mass screening of coeliac disease in children aged 12 years in two birth cohorts resulting in 296 seropositive children, of whom 242 were diagnosed with coeliac disease after duodenal biopsies. In this follow-up study, we wanted to identify new cases in the screening population that tested negative—either converting from potential coeliac disease (seropositive but normal duodenal mucosa) or converting from seronegative at screening to diagnosed coeliac diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…These studies must also address how mass screening compares to the expense and benefit derived from current targeted screening approaches. Second, more studies are needed on the natural history of potential celiac disease and transient celiac disease autoimmunity in order to determine the best practices in managing the clinical spectrum of patients who screen positive for celiac disease [47 ▪ ]. These additional studies will help round out a mass screening approach for policy stakeholders with respect to timing and frequency of screening and provide clinicians with evidence based recommendations on the management of the spectrum of individuals who screen positive.…”
Section: Discussionmentioning
confidence: 99%
“…These studies must also address how mass screening compares to the expense and benefit derived from current targeted screening approaches. Second, more studies are needed on the natural history of potential celiac disease and transient celiac disease autoimmunity in order to determine the best practices in managing the clinical spectrum of patients who screen positive for celiac disease [47 ▪ ]. These additional studies will help round out a mass screening approach for policy stakeholders with respect to timing and frequency of screening and provide clinicians with evidence based recommendations on the management of the spectrum of individuals who screen positive.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, case‐finding in children is not effective, 215,216 and in the United Kingdom 83‐91% of children with CD aged 15 years or younger are thought to be undiagnosed specially in lower socioeconomic groups 177 . In future, mass screening in late childhood may gain support as the most efficient public health measure to address unrecognised CD 216,217 …”
Section: Discussionmentioning
confidence: 99%
“…177 In future, mass screening in late childhood may gain support as the most efficient public health measure to address unrecognised CD. 216,217 Table 5 summarises future directions for diagnostics in CD.…”
Section: Gluten Challenge In Clinical Practicementioning
confidence: 99%
“…Although new approaches raise the hope for coeliacs, giving them a chance to return to gluten, for the time being, a cautionary appraisal of new therapies suggests that they may have a complementary role to gluten withdrawal, mainly to prevent inadvertent gluten contamination [ 5 , 6 ]. Consequently, several studies based on nutritional questionnaires, serological tests, and evaluating gluten immunogenic peptides (GIP) in stool and urine, have reported the non-adherence to a GFD in patients with CD to be between 10 and 88% in adults and between 2–77% in children [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, recent studies have suggested that the persistence of atrophy is due to the recurrence of gluten exposure [ 15 ].…”
Section: Introductionmentioning
confidence: 99%